Seasonal Variations in Algal Population of Ajanta Water–fall - Ashok. M. Chavan, Suhas M. Kamble, Milind. J. Jadhav and (Recent Research in Science and Technology, 2011)
In order to study the algal population of Ajanta caves water- fall, the visits were made frequently, in different seasons. The algal members were found from different divisions viz. Cyanophyta, Chlorophyta and Bacillariophyta. Cyanophycean members were found in good number as compare to Chlorophyceae and Bacillariophyceae. 12 genera found in Mansoon season 14 genera in winter season and 5 species in summer season, among all three seasons Mansoon season found very usefully for algal growth. At Ajanta caves water-fall Spirogyra plena found in maximum growth as compare to others.